Overview of the Brazilian odontological studies presented at a scientific meeting - SBPqO - Liliane Cristina BARBOSA; Tânia Adas SALIBA; Cléa Adas Saliba GARBIN; Suzely Adas Saliba MOIMAZ (Universidade Estadual Paulista, 2019)
Abstract Introduction It is important to verify the trends of Brazilian scientific production in the odontology area and the connection of study themes with the Ministry of Health's Priority Research Agenda. Objective Analyze the dental research profile of higher-education institutions presented at a Brazilian scientific event. Material and method This is a documentary analysis of the papers presented at the 35th SBPqO annual meeting, which included 3008 Brazilian studies. Also, 92 abstracts from the POAC category published between 2016 and 2018 were analyzed, verifying the subarea of public health, study type, and statistical tests employed. Result Of the 3008 works, 63.6% were from the Southeast region, 67% were conducted in public institutions, and 38.5% were supported by funding agencies (FAPESP, CAPES and CNPq). The titles analyzed using IRAMUTEQ presented predominance of themes related to dental caries epidemiology, quality of life, and chronic non-communicable diseases in children, pregnant women, women, elderly, and indigenous people. In the POAC category, the studies addressed health promotion (46%), oral health epidemiology (27%), health education (17%), and oral health care (10%). Statistical analysis was described in only 36% of the abstracts, of which 48% were from cross-sectional studies and 78% from surveys that employed association tests. Conclusion Brazilian scientific production in this filed came predominantly from the Southeast region and public institutions. There was connection between the themes and the Priority Research Agenda, and cross-sectional studies addressing health promotion predominated in POAC.